Marked regional variations in the prevalence of sickle cell disease and β-thalassemia in Saudi Arabia: Findings from the premarital screening and genetic counseling program - Ziad A. Memish; Tariq M. Owaidah; Mohamad Y. Saeedi (Springer, 2019)
Background: Hemoglobinopathies represent a major public health problem in Saudi Arabia (SA). Reports suggest that their higher prevalence is not evenly distributed in SA. Regional differences were studied in sickle cell disease and β-thalassemia and their at-risk marriages using national data. Methods: The carrier and case status of sickle cell disease and β-thalassemia were determined in couples approaching marriage between 2004 and 2009 using standard blood tests. Prevalence of both diseases and at-risk marriages in different SA administrative and geographical regions were calculated and compared. Results: A total of 15,72,140 men and women were examined over 6 years. This represented 0.06% of the entire population of Saudi Arabia. The prevalence of couples who tested positive for sickle cell was 45.1 (42.4 for carriers and 2.7 for cases) per 1000 persons examined. The prevalence was highest in the Eastern region (134.1 per 1000), followed by Southern and Western regions (55.6 and 28.5 per 1000, respectively) and lowest in Central and Northern regions (13.7 and 13.5 per 1000, respectively). The prevalence of couples testing positive for β-thalassemia was 18.5 (18.0 for carriers and 0.5 for cases) per 1000 persons examined. The prevalence was highest in the Eastern region (59.0), moderate in the Southern, Western and Central regions (14.2, 10.2, and 10.1 per 1000, respectively) and lowest in the Northern region (3.9). Conclusion: Vast regional differences in hemoglobinopathies among adult Saudis are being reported that may help policy makers better allocate resources of available preventive programs.